Optimal design of a commercial rubber isolator based on creep and creep-resistance analyses. (January 2022) - Leng, Dingxin; Yang, Yi; Li, Demin; Ma, Yong; Liu, Guijie; Li, Zhixiong
Creep is a common important physical phenomenon in rubber material, which induces the instability of geometrical dimension and deteriorates the mechanical performances. The present work develops an optimal design approach of a commercial rubber isolator based on creep analysis. First and foremost, a nonlinear creep constitutive model of rubber material is established, which can capture the hyper-elastic and time-dependent creep behaviors. Complete mechanical and creep tests of rubber materials are conducted, and material parameters are identified according to the experimental data. Then, the parametric finite element model of a rubber isolator is established, with which the time-dependent creep analysis based on the proposed creep constitutive model is conducted. The accuracy of the numerical creep analysis is validated at material level and structural component level. For engineering application, a sensitivity analysis and optimization design for creep-resistance of the rubber isolator is developed by combing finite element simulation and optimization method. The results show that creep-resistance characteristics of the optimal rubber isolator is largely improved, which provides a long-term stable behavior in vibration attenuation. The proposed method may provide an efficient tool for predicting the creep performance and optimal analysis of other commercial rubber-base products.